Blue‐light‐induced rapid chloroplast de‐anchoring in Vallisneria epidermal cells. Issue 1 (January 2015) - Sakai, Yuuki; Inoue, Shin‐Ichiro; Harada, Akiko; Shimazaki, Ken‐Ichiro; Takagi, Shingo
Abstract In the outer periclinal cytoplasm of leaf epidermal cells of an aquatic angiosperm Vallisneria, blue light induces "chloroplast de‐anchoring", a rapid decline in the resistance of chloroplasts against centrifugal force. Chloroplast de‐anchoring is known induced within 1 min of irradiation with high‐fluence‐rate blue light specifically, preceding the commencement of chloroplasts migration toward the anticlinal cytoplasm. However, its regulatory mechanism has remained elusive, although pharmacological analysis suggested that a calcium release from intracellular calcium stores is necessary for the response. In search of the responsible photoreceptors, immunoblotting analysis using antibodies against phototropins demonstrated that cross‐reactive polypeptides of 120‐kDa exist in the plasma‐membrane fraction prepared from the leaves. In vitro phosphorylation analysis revealed that 120‐kDa polypeptides were phosphorylated by exposure to blue light in a fluence‐dependent manner. The blue‐light‐induced phosphorylation activity was sensitive to a Ser/Thr kinase inhibitor, staurosporine, and unusually was retained at a high level for a long time in darkness. Furthermore, phototropin gene homologs (Vallisneria PHOTOTROPIN1 and PHOTOTROPIN2) expressed in leaves were isolated. We propose that calcium‐regulated chloroplast de‐anchoring, possibly mediated by phototropins, is an initial process of the blue‐light‐induced avoidance response of chloroplasts in Vallisneria.